2014
DOI: 10.3390/su6117967
|View full text |Cite
|
Sign up to set email alerts
|

Economic Sustainability of Italian Greenhouse Cherry Tomato

Abstract: Greenhouse tomato cultivation plays an important role in Sicily, being the primary production area in Italy, due to its favorable pedo-climatic conditions that permit extra-seasonal productions. In Sicily, more than half of greenhouse tomato production is derived from the Province of Ragusa on the southeastern coast, where especially cherry tomato typologies are cultivated. Over the last decade, the Ragusa Province has registered a decrease both in terms of greenhouse tomato area and harvested production due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 66 publications
(63 reference statements)
4
17
0
3
Order By: Relevance
“…However, this variety could be compared with other cherry tomato varieties. Lattauschke [33] and Testa et al [34] reported average yields of 15.0 and 16.6 kg·m −2 , respectively. The exact durations of the seasons were not declared.…”
Section: Discussionmentioning
confidence: 99%
“…However, this variety could be compared with other cherry tomato varieties. Lattauschke [33] and Testa et al [34] reported average yields of 15.0 and 16.6 kg·m −2 , respectively. The exact durations of the seasons were not declared.…”
Section: Discussionmentioning
confidence: 99%
“…A "major" disease usually affects yield, as has been reported for RFSm in many literature (Nessa et al, 2015). Besides, a disease, when impacts yield, also reduces the economic sustainability of a crop by lowering farmers' income (Kuosmanen et al, 2013;Spiertz, 2013;Testa et al, 2014;Sgroi et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
“…There are many weed management techniques that can be lead to reduced herbicide dependence, as direct-seeding, competitive varieties, increased seeding rates, strategic fertilizer placement, growing silage and cover crops, all these have excellent potential to suppress weed growth (Harker and Blackshaw, 2009). Crop residues hold a great prospect for meeting some of those demands and have more readily applicable in agro ecosystems (Alsaadawi et al, 2013;Testa et al, 2014;Sgroi et al, 2014). This approach (Crop residue) can be used in weeds management by two ways; it can be used by selecting an appropriate residue of crop variety then incorporating it in soil, Also it can used by applying residues or straw as mulches on soil surface in a rotational sequence that allows residues to remain in the field (Alsaadawi and Dayan, 2009).…”
Section: Introductionmentioning
confidence: 99%